Microbial specialists in below‐grade foundation walls in Scandinavia. (17th February 2014) - Nunez, M.; Hammer, H.
Abstract Below‐grade foundation walls are often exposed to excessive moisture by water infiltration, condensation, leakage, or lack of ventilation. Microbial growth in these structures depends largely on environmental factors, elapsed time, and the type of building materials and construction setup. The ecological preferences of Actinomycetes (Actinobacteria) and the molds Ascotricha chartarum, Myxotrichum chartarum (Ascomycota), Geomyces pannorum, and Monocillium sp. (Hyphomycetes) have been addressed based on analyses of 1764 samples collected in below‐grade spaces during the period of 2001–2012. Our results show a significant correlation between these taxa and moist foundation walls as ecological niches. Substrate preference was the strongest predictor of taxa distribution within the wall, but the taxa's physiological needs, together with gradients of abiotic factors within the wall structure, also played a role. Our study describes for the first time how the wall environment affects microbial growth.